Persistence in the Private Debt-to-GDP Ratio: Evidence from 43 OECD Countries - Guglielmo Maria Caporale; Luis A. Gil-Ala\~na; Maria Malmierca (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper investigates the degree of persistence of the private debt-to-GDP ratio in 43 OECE countries by estimating the fractional integration parameter of each series. Almost all of them are found to be highly persistent, with orders of integration around or above 1. The only exception is Argentina, where the series appears to be mean-reverting. These results highlight the key importance of macroprudential policy as one of the pillars of macro policy.
Keywords: C22; G30; G51; 330; persistence; fractional integration; private debt